Oxide composite solid electrolyte membrane and preparation method and application thereof

Through the composite and in-situ thermal polymerization technology of garnet oxide and PET fiber membrane, the problem of easy shrinkage and fracture in large-scale production of oxide solid electrolyte membrane is solved, and oxide composite with low internal resistance and high mechanical strength is achieved The membrane is suitable for industrial production and reduces interface resistance in lithium-ion batteries, improving battery safety and performance.

CN114649586BActive Publication Date: 2025-01-03ZHEJIANG NARADA POWER SOURCE CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210242572.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-11
Publication Date
2025-01-03
Estimated Expiration
2042-03-11

AI Technical Summary

Technical Problem

The existing oxide solid electrolyte membranes are prone to shrink and break during large-scale production, and the thickness is too high, resulting in an increase in the internal resistance of the battery, making it difficult to build a complete oxide lithium conduction channel, and the mechanical strength is not enough to meet the requirements of the coating and drying process.

Method used

The garnet oxide electrolyte is combined with alkali-resistant polymer and PET fiber membrane, combined with in-situ thermal polymerization technology of triethylene glycol dimethacrylate, and the coating of 'base film on top and slurry on bottom' is adopted. Process to build an ultra-thin oxide composite solid electrolyte membrane to ensure the integrity and mechanical strength of the lithium conduction channel.

Benefits of technology

It realizes a low internal resistance and high mechanical strength oxide composite solid electrolyte membrane, which is suitable for industrial production, avoids brittle cracking problems, and reduces interface resistance in lithium-ion batteries, improving the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114649586B_ABST
    Figure CN114649586B_ABST
Patent Text Reader

Abstract

The present invention discloses an oxide composite solid electrolyte membrane and a preparation method and application thereof, which is obtained by in-situ thermal polymerization of a composite membrane made of a garnet oxide electrolyte, an alkali-resistant polymer and a fiber membrane and a solution containing triethylene glycol dimethacrylate. The present invention uses a PET fiber membrane to realize batch preparation of an ultra-thin oxide solid electrolyte membrane, constructs a complete oxide lithium-conducting channel, and the ultra-thin thickness can reduce the internal resistance of the battery. The mechanical strength can meet the requirements of the winding and unwinding process of the coating and drying process, and it does not shrink or break, and can realize large-scale production and preparation; the coating process of "base film on top and slurry on the bottom" is adopted to realize the construction of the oxide lithium-conducting channel at a lower load, better cover the large pores of the fiber membrane, and prevent the battery from micro-short circuit; the garnet oxide electrolyte / PET composite membrane is in-situ thermally polymerized with TEGDMA to solve the electrode / electrolyte solid-solid interface problem caused by the rigidity of the oxide electrolyte and reduce the interface resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium batteries and relates to a solid electrolyte membrane, in particular to an oxide composite solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Garnet oxide solid electrolyte (LLZO) has high ion conductivity, wide electrochemical window, good chemical stability and high temperature stability to positive and negative electrodes, but the particles are very rigid and sintered into electrolyte sheets, which are easy to break. The thickness needs to reach hundreds of microns to barely ensure that it will not break during transfer and use. However, too high electrolyte thickness increases the internal resistance of the battery. Usually, oxide electrolytes are compounded with polymer solid electrolytes with good soft viscosity, which can prevent brittle fracture and improve the interface contact between electrolyte and electrode.

[0003] The mechanical strength of polymers is limited, especially in quasi-solid-state batteries with a small amount of electrolyte added. The strength of polymers decreases after absorbing liquid, and the positive and negative electrodes are prone to local contact under pressure and micro-short circuits. In order to improve the strength of oxide / polymer composite electrolytes and isolate the contact between positive and negative electrodes, existing technologies use ordinary polyolefin separators or cellulose membranes as carriers. Polyolefin separators are thin (less than 25μm) and have high strength, but have small pores, and oxide electrolytes cannot pass through, blocking the oxide lithium-conducting channels. Cellulose membranes are usually 20 to 40μm thick (too high thickness will affect the internal resistance and volumetric specific energy of the battery), with large pores that can pass through oxide electrolytes, but the strength is poor within this thickness range. During the winding and unwinding process of electrolyte slurry coating and drying, the cellulose membrane is very easy to shrink and break, and is not suitable for large-scale production applications. Summary of the invention

[0004] The purpose of the present invention is to solve the defects of existing oxide solid electrolyte membranes that are not suitable for large-scale production and are easy to shrink and break, and to provide an oxide composite solid electrolyte membrane. The oxide composite solid electrolyte membrane has high ionic conductivity and good contact with the electrode interface. It can not only ensure the construction of a complete oxide lithium-conducting channel, but also has a low thickness to ensure low internal resistance. It also has good mechanical strength to meet the requirements of winding and unwinding without shrinkage or breakage during coating and drying, and is suitable for industrial production.

[0005] The present invention also provides a preparation method and application of the oxide composite solid electrolyte membrane.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] An oxide composite solid electrolyte membrane is obtained by in-situ thermal polymerization of a composite membrane made of a garnet oxide electrolyte, an alkali-resistant polymer and a fiber membrane and a solution containing triethylene glycol dimethacrylate.

[0008] In the present invention, the garnet-type oxide electrolyte has high ion conductivity, wide electrochemical window, and good chemical stability and high-temperature stability to positive and negative electrodes.

[0009] Polyethylene terephthalate (PET) fiber membrane has large pores between fibers that allow oxide electrolytes to pass through, which is beneficial for building a complete oxide lithium-conducting channel. It also has a thin thickness (10-25 μm) and sufficient strength, and can meet the requirements of the winding and unwinding process during electrolyte coating and drying without increasing the internal resistance. The melting point is higher than that of ordinary polyolefin separators (>200°C), and the combination with oxide electrolytes can ensure excellent high-temperature stability and improve battery safety.

[0010] The role of the alkali-resistant polymer is to adhere the garnet oxide electrolyte to the PET fiber film. N-methylpyrrolidone (NMP) is a commonly used solvent in the production of lithium-ion batteries, and has mature recycling processes and equipment, but the garnet oxide electrolyte LLZO / NMP mixed solution is strongly alkaline, especially when LLZO accounts for a high proportion, PVDF, HFP-PVDF and other commonly used oily binders will undergo HF removal in the mixed solution and discolor and gel, affecting the preparation of the electrolyte slurry. The present invention uses nitrile rubber (NBR) or acrylic polymers, which have better alkali resistance, maintain chemical stability in a high-concentration LLZO / NMP system, and can prepare a uniform and stable electrolyte slurry.

[0011] Electrolyte slurry is usually coated by a scraping process, and the upper electrolyte slurry is coated on the lower substrate. However, on the PET fiber membrane used in the present invention, due to the large pore size of the PET fiber membrane, the electrolyte slurry will penetrate to the other side of the membrane under the action of gravity. In order to make the oxide electrolyte cover the large pores between the PET fibers better and prevent the positive and negative electrodes from being exposed due to local micro-short circuits, the coating method of "slurry on top and base film on bottom" requires coating more oxide electrolyte, which reduces the weight specific energy of the battery and also increases the cost of the electrolyte membrane. The present invention adopts the "base film on top and slurry on the bottom" coating process, the PET fiber membrane is located above the micro-concave roller (or wire rod), and is wound and unwound at a certain speed (10-20mm / s). After the electrolyte slurry enters the material tank from the bottom of the material tank, the rotating micro-concave roller (or wire rod) brings the slurry to the top and adheres to the PET fiber membrane moving at a uniform speed. Using this coating process, the oxide electrolyte is mainly enriched on one side and a small amount penetrates to the other side, which can realize the construction of oxide lithium-conducting channels at a lower loading amount and better cover the large pores of the fiber membrane to prevent battery micro-short circuits.

[0012] On the basis of garnet oxide electrolyte / PET composite membrane, combined with triethylene glycol dimethacrylate (TEGDMA) in-situ thermal polymerization technology, a solution containing TEGDMA monomer is injected after the battery is assembled, and heated and polymerized at 60℃~70℃. This can improve the wetting between the electrolyte and the electrode material, solve the electrode / electrolyte solid-solid interface problem caused by the rigidity of the oxide electrolyte, and reduce the interface resistance.

[0013] As a preferred embodiment of the present invention, the garnet-type oxide electrolyte comprises Li7La3Zr2O 12 and Li 7-x Ln3Z 2-x M x O 12 , wherein M = Ta, Nb, Ga or Al, 0.25≤x≤2; the particle size of the garnet-type oxide electrolyte is 100 to 600 nm.

[0014] As a preferred embodiment of the present invention, the alkali-resistant polymer comprises at least one of nitrile rubber and acrylic polymer; and the mass ratio of the garnet-type oxide electrolyte to the alkali-resistant polymer is 7:3 to 20:1.

[0015] As a preferred solution of the present invention, the fiber membrane is a polyethylene terephthalate fiber membrane with a thickness of 10 to 25 μm and a fiber diameter of 1 to 10 μm.

[0016] As a preferred embodiment of the present invention, the solution containing triethylene glycol dimethacrylate comprises triethylene glycol dimethacrylate, lithium salt, organic solvent, film-forming additive and thermal initiator.

[0017] As a preferred embodiment of the present invention, the solution containing triethylene glycol dimethacrylate comprises, by mass percentage, 5% to 40% of triethylene glycol dimethacrylate, 10% to 30% of lithium salt, 40% to 80% of organic solvent, 0.5% to 5% of film-forming additive and 0.05% to 1% of thermal initiator.

[0018] As a preferred embodiment of the present invention, the lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonylimide), lithium tetrafluoroborate, and lithium dioxalatoborate; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate; the film-forming additive includes fluoroethylene carbonate, vinylene carbonate, or a mixture of the two; and the thermal initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptylnitrile, dimethyl azobisisobutyrate, methyl ethyl ketone peroxide, and tert-butyl benzoyl peroxide.

[0019] As a preferred embodiment of the present invention, the composite solid electrolyte membrane has a thickness of 20 to 40 μm and a room temperature ionic conductivity of 10 -5 ~10 -3 S / cm, and the electrochemical window is 0-5V.

[0020] The above-mentioned method for preparing the oxide composite solid electrolyte membrane comprises the following steps:

[0021] (1) adding a garnet-type oxide electrolyte and a solvent, and wet-milling the mixture at a rotation speed of 100 rpm to 400 rpm for 2 h to 6 h to obtain a uniformly dispersed mixed solution;

[0022] (2) uniformly dispersing the alkali-resistant polymer in a solvent, adding the mixed solution of step (1), and further stirring and dispersing to obtain a uniform and stable electrolyte slurry;

[0023] (3) A coating process with a micro-concave roller or wire rod with the base film on the top and the slurry on the bottom is adopted, and the polyethylene terephthalate fiber film is coated on the top of the micro-concave roller or wire rod for winding and unwinding. After the electrolyte slurry of step (2) enters the material tank from the bottom of the material tank, the rotating micro-concave roller or wire rod brings the slurry to the top and adheres to the polyethylene terephthalate fiber film moving at a uniform speed;

[0024] (4) The polyethylene terephthalate fiber film coated with the slurry in step (3) is uniformly fed into a drying oven for drying to remove the solvent at a temperature of 70° C. to 110° C., thereby obtaining a rolled composite film;

[0025] (5) A battery is manufactured based on the positive electrode, the negative electrode and the composite membrane of step (4), a solution containing triethylene glycol dimethacrylate is prepared, injected into the battery and allowed to stand to allow the solution to fully infiltrate the electrode and the composite membrane, and then in-situ thermal polymerization is carried out at 60° C. to 70° C. for 2 h to 24 h to obtain an oxide composite solid electrolyte membrane.

[0026] Application of the above oxide composite solid electrolyte membrane or the oxide composite solid electrolyte membrane prepared by the above preparation method in the fields of lithium-ion batteries, lithium-sulfur batteries and lithium-air batteries.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) The present invention uses PET fiber membrane to realize batch preparation of ultra-thin oxide solid electrolyte membrane, which not only constructs a complete oxide lithium-conducting channel, but also reduces the internal resistance of the battery with ultra-thin thickness. At the same time, the mechanical strength can meet the requirements of the winding and unwinding process of the coating and drying process, without shrinkage or breakage, and can realize large-scale production and preparation;

[0029] 2) The present invention adopts a coating process of "base film on top and slurry on the bottom", which can realize the construction of oxide lithium-conducting channels at a lower loading amount, and better cover the macropores of the fiber membrane to prevent micro short circuits of the battery;

[0030] 3) The garnet oxide electrolyte / PET composite film of the present invention is composited with TEGDMA by in-situ thermal polymerization to solve the electrode / electrolyte solid-solid interface problem caused by the rigidity of the oxide electrolyte and reduce the interface resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM photograph of the PET fiber membrane of Example 1.

[0032] Figure 2 This is a SEM photograph of the LLZTO / PET composite film of Example 1.

[0033] Figure 3 This is the discharge capacity of the solid-state battery of Example 1 at 0.3C at room temperature.

[0034] Figure 4 It is the discharge capacity retention rate of the solid-state battery of Example 1 at 0.3C at room temperature. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] The raw materials used in the present invention can all be purchased from the market.

[0037] Embodiment 1:

[0038] This embodiment provides a method for preparing an oxide composite solid electrolyte membrane, comprising:

[0039] 800g Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) powder and 400g NMP were added to a ball mill and ball milled at 300rpm for 4h to obtain a uniformly dispersed LLZTO / NMP mixed solution. 80g nitrile rubber (NBR) was added to 800g NMP and stirred for 4h. After uniform dispersion, the above LLZTO / NMP mixed solution was added and stirred for 24h to obtain a uniform and stable LLZTO / NBR slurry.

[0040] The 18μm thick PET fiber film was coated on the micro-concave roller and rolled up after passing through the drying tunnel at a speed of 10mm / s. The LLZTO / NBR slurry was pumped into the bottom of the trough and brought from the bottom to the top by the rotating micro-concave roller, adhering to the PET film. The PET fiber film coated with the slurry was uniformly entered into the 95℃ drying tunnel to dry and remove NMP, and a rolled LLZTO / PET composite film was obtained. The SEM photos before and after LLZTO coating are shown in Figure 1 and Figure 2 The diameter of PET fiber is about 5μm. After coating with LLZTO, the pores between the fibers are well covered by the LLZTO coating, eliminating the possibility of micro short circuit caused by exposed pores.

[0041] Weigh 2.46 g of lithium difluorooxalatoborate, 1.35 g of TEGDMA, 6.2 g of ethylene carbonate, 4.64 g of ethyl methyl carbonate, 4.64 g of diethyl carbonate, 0.1 g of vinylene carbonate, 0.6 g of fluoroethylene carbonate and 0.02 g of azobisisobutyronitrile, stir and dissolve uniformly to obtain a TEGDMA precursor solution.

[0042] In order to characterize the electrochemical properties of the composite membrane, such as ionic conductivity, the TEGDMA precursor solution was dropped onto the LLZTO / PET fiber composite membrane. The composite membrane was clamped between two upper and lower glass plates, a pressure of 60 kg was applied to it, and it was kept at 60°C for 8 h for in-situ thermal polymerization to obtain a LLZTO / TEGDMA / PET composite membrane with a thickness of about 28 μm.

[0043] The LLZTO / TEGDMA / PET composite membrane prepared in this example was assembled into a symmetrical blocked button cell, and a stainless steel gasket was used as a blocking electrode. The battery was subjected to an AC impedance test with a frequency range of 2M to 0.1 Hz and an amplitude of 10 mV. According to the obtained AC impedance spectrum, the room temperature ionic conductivity of the composite membrane was calculated to be 4.2×10 -4 S / cm.

[0044] The LLZTO / TEGDMA / PET composite film prepared in this example was assembled into a stainless steel / Li button cell, and a linear sweep voltammetry test was performed on it. The voltage range was open circuit voltage (OCP) ~ 6V (vs. Li / Li + ), with a scanning rate of 1 mV / s, the electrochemical stability window of the composite film was measured to be 4.5 V.

[0045] The composite solid electrolyte technology is used to assemble a 6Ah soft-pack lithium-ion battery, with the positive electrode made of LiNi 0.6 Co 0.2 Mn 0.2O2, carbon nanotubes and PVDF are composed in a mass ratio of 95:3:2. The negative electrode is composed of silicon dioxide / graphite composite, carbon nanotubes and polyacrylonitrile in a mass ratio of 95:3:2, and LLZTO / PET composite membrane is used as a separator. The above TEGDMA solution is injected into the assembled dry battery cell, and it is allowed to stand for 1 day to ensure that the solution is fully infiltrated with the electrode and the composite membrane. Then, a pressure of 0.1MPa is applied to the battery cell, and it is kept at 60℃ for 8h for in-situ thermal polymerization. The assembled soft-pack battery is charged and discharged at room temperature and 0.3C. The performance is as follows Figure 3 and Figure 4 As shown, the initial capacity is 6.02Ah, and the capacity retention rate is 94.9% after 287 cycles.

[0046] Embodiment 2:

[0047] This embodiment provides a method for preparing an oxide composite solid electrolyte membrane, comprising:

[0048] 600g Li 6.4 Ln3Z 1.4 Nb 0.6 O 12 (LLZNO) powder and 400g NMP were added to a ball mill and ball milled at 200rpm for 6h to obtain a uniformly dispersed LLZNO / NMP mixed solution. 100g nitrile rubber (NBR) was added to 800g NMP and stirred for 4h. After uniform dispersion, the above LLZNO / NMP mixed solution was added and stirred for 24h to obtain a uniform and stable LLZNO / NBR slurry.

[0049] A 20μm thick PET fiber film is coated on the wire rod and rolled up after passing through the drying tunnel at a speed of 15mm / s. The LLZNO / NBR slurry is pumped into the bottom of the trough and brought from the bottom to the top by the rotating wire rod, adhering to the PET film. The PET fiber film coated with the slurry enters the 100℃ drying tunnel at a uniform speed to dry and remove NMP, and a rolled LLZNO / PET composite film is obtained.

[0050] Weigh 1.44 g of lithium difluorooxalatoborate, 1.52 g of lithium hexafluorophosphate, 1.35 g of TEGDMA, 6.2 g of ethylene carbonate, 9.24 g of dimethyl carbonate, 0.3 g of vinylene carbonate, 0.4 g of fluoroethylene carbonate and 0.02 g of dimethyl azobisisobutyrate, stir and dissolve uniformly to obtain a TEGDMA precursor solution.

[0051] In order to characterize the electrochemical properties of the composite membrane, such as ionic conductivity, the TEGDMA precursor solution was dropped onto the LLZNO / PET fiber composite membrane. The composite membrane was clamped between two upper and lower glass plates, a pressure of 30 kg was applied to it, and it was kept at 70°C for 4 h for in-situ thermal polymerization to obtain a LLZNO / TEGDMA / PET composite membrane with a thickness of about 26 μm.

[0052] The LLZNO / TEGDMA / PET composite membrane prepared in this example was assembled into a symmetrical blocked button cell, and a stainless steel gasket was used as a blocking electrode. The battery was subjected to an AC impedance test with a frequency range of 2M to 0.1 Hz and an amplitude of 10 mV. According to the obtained AC impedance spectrum, the room temperature ionic conductivity of the composite membrane was calculated to be 2.5×10 -4 S / cm.

[0053] The LLZNO / TEGDMA / PET composite film prepared in this example was assembled into a stainless steel / Li button cell, and a linear sweep voltammetry test was performed on it. The voltage range was open circuit voltage (OCP) ~ 6V (vs. Li / Li + ), with a scanning rate of 1 mV / s, the electrochemical stability window of the composite film was measured to be 4.55 V.

[0054] The composite solid electrolyte technology is used to assemble a 6Ah soft-pack lithium-ion battery, with the positive electrode made of LiNi 0.6 Co 0.2 Mn 0.2 O2, carbon nanotubes and PVDF are composed in a mass ratio of 95:3:2, the negative electrode is composed of silicon oxide / graphite composite, carbon nanotubes and polyacrylonitrile in a mass ratio of 95:3:2, and LLZNO / PET composite membrane is used as a separator. The above TEGDMA solution is injected into the assembled dry battery cell, and it is left to stand for 1 day to ensure that the solution is fully infiltrated with the electrode and the composite membrane. Then, a pressure of 0.5MPa is applied to the battery cell, and it is kept at 70℃ for 4h for in-situ thermal polymerization. The assembled soft-pack battery is charged and discharged at room temperature and 0.3C. The initial capacity is 5.96Ah, and the capacity retention rate is 92.1% after 250 cycles.

[0055] Embodiment 3:

[0056] This embodiment provides a method for preparing an oxide composite solid electrolyte membrane, comprising:

[0057] 800g Li7La3Zr2O 12(LLZO) powder and 400g NMP were added to a ball mill and ball milled at 400rpm for 2h to obtain a uniformly dispersed LLZO / NMP mixed solution. 60g polyacrylate was added to 800g NMP and stirred for 4h. After uniform dispersion, the above LLZO / NMP mixed solution was added and stirred for 24h to obtain a uniform and stable LLZO / NBR slurry.

[0058] A 25μm thick PET fiber film is placed on the micro-concave roller and rolled up after passing through a drying tunnel at a speed of 20mm / s. The LLZO / NBR slurry is pumped into the bottom of the trough and brought from the bottom to the top by the rotating micro-concave roller, adhering to the PET film. The PET fiber film coated with the slurry enters the 85℃ drying tunnel at a uniform speed to dry and remove NMP, and a rolled LLZO / PET composite film is obtained.

[0059] Weigh 2.87 g of lithium bis(trifluoromethylsulfonyl)imide, 1.52 g of lithium hexafluorophosphate, 5 g of TEGDMA, 3.2 g of ethylene carbonate, 3.3 g of ethyl methyl carbonate, 3.3 g of diethyl carbonate, 0.5 g of vinylene carbonate and 0.01 g of benzoyl peroxide, stir and dissolve them uniformly to obtain a TEGDMA precursor solution.

[0060] In order to characterize the electrochemical properties of the composite membrane, such as ionic conductivity, the TEGDMA precursor solution was dropped onto the LLZO / PET fiber composite membrane. The composite membrane was clamped between two upper and lower glass plates, a pressure of 50 kg was applied to it, and it was kept at 60°C for 24 h for in-situ thermal polymerization to obtain a LLZO / TEGDMA / PET composite membrane with a thickness of about 30 μm.

[0061] The LLZO / TEGDMA / PET composite membrane prepared in this example was assembled into a symmetrical blocked button cell, and a stainless steel gasket was used as a blocking electrode. The battery was subjected to an AC impedance test with a frequency range of 2M to 0.1 Hz and an amplitude of 10 mV. According to the obtained AC impedance spectrum, the room temperature ionic conductivity of the composite membrane was calculated to be 1.2×10 -4 S / cm.

[0062] The LLZO / TEGDMA / PET composite film prepared in this example was assembled into a stainless steel / Li button cell, and a linear sweep voltammetry test was performed on it. The voltage range was open circuit voltage (OCP) ~ 6V (vs. Li / Li + ), with a scanning rate of 1 mV / s, the electrochemical stability window of the composite film was measured to be 4.5 V.

[0063] The composite solid electrolyte technology is used to assemble a 6Ah soft-pack lithium-ion battery, with the positive electrode made of LiNi 0.6 Co 0.2 Mn 0.2O2, carbon nanotubes and PVDF are composed in a mass ratio of 95:3:2, the negative electrode is composed of silicon oxide / graphite composite, carbon nanotubes and polyacrylonitrile in a mass ratio of 95:3:2, and LLZO / PET composite film is used as a separator. The above TEGDMA solution is injected into the assembled dry battery cell, and it is left to stand for 1 day to ensure that the solution is fully infiltrated with the electrode and the composite membrane. Then, a pressure of 1MPa is applied to the battery cell, and it is kept at 60℃ for 24h for in-situ thermal polymerization. The assembled soft-pack battery is charged and discharged at room temperature and 0.3C. The initial capacity is 6.01Ah, and the capacity retention rate is 95% after 250 cycles.

[0064] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An oxide composite solid electrolyte membrane, characterized in that: The oxide composite solid electrolyte membrane is obtained by in-situ thermal polymerization of a composite membrane made of a garnet oxide electrolyte, an alkali-resistant polymer and a fiber membrane and a solution containing triethylene glycol dimethacrylate; the alkali-resistant polymer comprises at least one of nitrile rubber and an acrylate polymer; the mass ratio of the garnet oxide electrolyte to the alkali-resistant polymer is 7:3 to 20:1; the fiber membrane is a polyethylene terephthalate fiber membrane with a thickness of 10 to 25 μm and a fiber diameter of 1 to 10 μm; the garnet oxide electrolyte comprises Li7La3Zr2O 12 and Li 7-x LqCy 2-x M x O 12 , wherein M = Ta, Nb, Ga or Al, 0.25≤x≤2; the particle size of the garnet-type oxide electrolyte is 100 to 600 nm.

2. An oxide composite solid electrolyte membrane according to claim 1, characterized in that: The triethylene glycol dimethacrylate-containing solution comprises triethylene glycol dimethacrylate, lithium salt, organic solvent, film-forming additive and thermal initiator.

3. An oxide composite solid electrolyte membrane according to claim 2, characterized in that: The triethylene glycol dimethacrylate-containing solution comprises, by mass percentage, 5% to 40% of triethylene glycol dimethacrylate, 10% to 30% of lithium salt, 40% to 80% of organic solvent, 0.5% to 5% of film-forming additive and 0.05% to 1% of thermal initiator.

4. An oxide composite solid electrolyte membrane according to claim 2 or 3, characterized in that: The lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonylimide), lithium tetrafluoroborate, and lithium dioxalatoborate; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate; the film-forming additive includes fluoroethylene carbonate, vinylene carbonate, or a mixture of the two; the thermal initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptylnitrile, dimethyl azobisisobutyrate, methyl ethyl ketone peroxide, and tert-butyl benzoyl peroxide.

5. The oxide composite solid electrolyte membrane according to claim 1, characterized in that: The composite solid electrolyte membrane has a thickness of 20-40 μm and a room temperature ionic conductivity of 10 -5 ~10 -3 S / cm, and the electrochemical window is 0-5V.

6. A method for preparing an oxide composite solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) adding a garnet-type oxide electrolyte and a solvent, and wet-milling the mixture at a rotation speed of 100 rpm to 400 rpm for 2 h to 6 h to obtain a uniformly dispersed mixed solution; (2) uniformly dispersing the alkali-resistant polymer in a solvent, adding the mixed solution of step (1), and further stirring and dispersing to obtain a uniform and stable electrolyte slurry; (3) A coating process with a micro-concave roller or wire rod with the base film on the top and the slurry on the bottom is adopted, and the polyethylene terephthalate fiber film is coated on the top of the micro-concave roller or wire rod for winding and unwinding. After the electrolyte slurry of step (2) enters the material tank from the bottom of the material tank, the rotating micro-concave roller or wire rod brings the slurry to the top and adheres to the polyethylene terephthalate fiber film moving at a uniform speed; (4) The polyethylene terephthalate fiber film coated with the slurry in step (3) is uniformly fed into a drying oven for drying to remove the solvent at a temperature of 70° C. to 110° C., thereby obtaining a rolled composite film; (5) A battery is manufactured based on the positive electrode, the negative electrode and the composite membrane of step (4), a solution containing triethylene glycol dimethacrylate is prepared, injected into the battery and allowed to stand to allow the solution to fully infiltrate the electrode and the composite membrane, and then in-situ thermal polymerization is carried out at 60° C. to 70° C. for 2 h to 24 h to obtain an oxide composite solid electrolyte membrane.

7. An application of an oxide composite solid electrolyte membrane, characterized in that: Application of the oxide composite solid electrolyte membrane prepared by the preparation method described in claim 6 in the fields of lithium-ion batteries, lithium-sulfur batteries and lithium-air batteries.